Weaning of proton pump inhibitors in patients with suspected laryngopharyngeal reflux disease. (21st July 2017) - Lin, R. Jun; Sridharan, Shaum; Smith, Libby J.; Young, VyVy N.; Rosen, Clark A.
Abstract : Objective: To evaluate the feasibility of a proton pump inhibitor (PPI) weaning protocol in a cohort of patients following successful empiric treatment for suspected laryngopharyngeal reflux disease (LPRD). Study Design: Retrospective chart review. Methods: LPRD patients were weaned from PPIs using a standardized weaning protocol. Symptom recurrence rate following PPI wean and present PPI use were determined. All numeric data were analyzed. The setting was a tertiary laryngology practice. The subjects were patients who had a positive response to empiric treatment for LPRD and subsequently were weaned from PPI therapy. Results: Thirty‐five patients with suspected LPRD were instructed to wean from PPI after successful empiric treatment of their LPRD symptoms from July 2013 to September 2015. Twenty‐three patients (66%) remained symptom‐free post‐wean. Twelve patients (34%) had symptom recurrence post‐wean; of those, 11 of them (92%) needed to go back on a PPI. Median durations of follow‐up for the unsuccessful wean group and the successful wean group were 13 (range 6–29) months and 18 (range 6–38) months, respectively. Pre‐wean and post‐wean reflux symptom index (RSI) scores in the unsuccessful wean group were 7.7 ± 5.6 and 12.9 ± 6 ( P  = .11). Pre‐wean and post‐wean RSI scores in the successful wean group were 8.1 ± 6.5 and 8.1 ± 9.0 ( P  < .99). Body mass index (BMI) was found to be a significant predictor of failure to wean (odds ratio = 0.72, 95% confidence interval = 0.55–0.95) after controlling for age, sex, PPI treatment duration, and PPI regime. None of the other covariates were found to be significant predictors of failure of PPI wean. Conclusion: Approximately 66% of patients who were on PPIs for LPRD were successfully weaned. High BMI was significantly predictive of failure to wean. Level of Evidence: 4. Laryngoscope, 128:133–137, 2018